CRISPR : ERA BARU TERAPI PENYAKIT PERNAPASAN: MENGATASI PENYAKIT PERNAPASAN DENGAN CRISPR-CAS9 - Fadhila, Luthfiya Nur; Sanjaya, I Kadek Ari (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2024)
Background: Respiratory diseases are a significant global health burden, affecting the quality of life of millions of people worldwide. Genetic therapy using CRISPR-Cas9 technology has become a paradigm shift in the treatment of respiratory diseases. This article presents a comprehensive literature review on the use of CRISPR-Cas9 in addressing respiratory diseases, including cystic fibrosis, chronic obstructive pulmonary disease (COPD), and SARS-CoV. This review includes an introduction that provides background on the importance of respiratory disease therapy and the potential of CRISPR-Cas9 in overcoming these challenges. Methods: The literature search method was conducted through scientific databases such as PubMed, Google Scholar, and Scopus. The results reveal that CRISPR-Cas9 can be used to edit genes related to respiratory diseases, reduce inflammation, excessive mucus production, and lung tissue damage, as well as detect the presence of these diseases. Discussion: The discussion highlights the effectiveness of CRISPR-Cas9 based on experimental studies on animal models and in vitro experiments. Challenges that need to be addressed include the efficiency and precision of the technology, long-term safety, and effective delivery. Conclusion: The potential of CRISPR-Cas9 as a therapy for respiratory diseases emphasizes the need for further research and technological development to optimize the effectiveness and safety of this therapy. Thus, breakthroughs in respiratory disease therapy with CRISPR-Cas9 have the potential to improve the health and well-being of the global population. Keywords: CRISPR-Cas9, gene editing, genetic therapy, respiratory diseases